Perceptions of People with Special Needs Regarding Autonomous Vehicles and Implication on the Design of Mobility as a Service to Foster Social Inclusion - Nanchen, Benjamin; Ramseyer, Randolf; Grèzes, Sandra; Wyer, Mélanie; Gervaix, Alain; Juon, Dominic; Fragnière, Emmanuel (Frontiers in Human Dynamics, 2022)
Worldwide, more than one billion people live with disabilities. People with disabilities (PWD) have needs in terms of autonomy, social participation and inclusion. Mobility is one condition for them to be included in society and participate in social life. Autonomous vehicles (AVs) can be part of the concept of Mobility as a Service (MaaS) that enables us to rethink the policy of mobility. However, the way these new autonomous mobility services are designed could exclude PWD. To prevent that, universal design principles and inclusive design could help policymakers and public transport companies design new means of transport that are accessible to all. However, perceptions of PWD regarding MaaS in general and AVs are not well documented. This article presents qualitative research about these perceptions. Eight semi-directive interviews were thus carried out on the subject. Based on these findings, we developed an integrative model to accompany and orchestrate such AV design developments. This integrative model will help policymakers and public transport companies rethink mobility concepts while incorporating AVs and make them accessible to ensure the social inclusion of PWD.